Hidden Feature Weighted Deep Ranking Model (Hfwdr): A Novel Deep Learning Approach to Investigate the Nuanced Aesthetic Value of the Elderly Furniture Design & Cultural Identity - Lu, Jing; Musdi, Hj Shanat (IJISAE, 2024)
The aesthetic value of elderly furniture design transcends mere functionality, embodying a rich tapestry of cultural heritage and historical significance. Rooted in traditional craftsmanship and informed by generations of cultural evolution, elderly furniture design carries with it a sense of timelessness and authenticity. Cultural identity and the evolution of the times are intertwined forces that shape societies, influencing everything from art and architecture to social norms and values. Cultural identity encompasses the unique customs, traditions, and beliefs that define a community or group, providing a sense of belonging and continuity across generations. This study investigates the aesthetic value of elderly furniture design, exploring its connection to cultural identity and the evolving socio-cultural landscape. By employing the Hidden Feature Weighted Deep Ranking Model (HFWDR), a novel deep learning approach, the research delves into the nuanced features of elderly furniture designs that resonate with cultural heritage and contemporary sensibilities. Through an analysis of design elements, material choices, and cultural motifs, the study uncovers the intrinsic relationship between furniture aesthetics and cultural identity, shedding light on how design evolves over time while retaining cultural authenticity. The HFWDR model, with its ability to capture hidden features and prioritize their significance in ranking, offers a comprehensive framework for evaluating and understanding the aesthetic evolution of elderly furniture design within the context of changing cultural dynamics. the HFWDR model assigned numerical values to hidden features such as symmetry, material quality, and historical relevance, with scores ranging from 0 to 100, indicating the degree of importance in determining the aesthetic value of elderly furniture designs.